Pengaruh Motivasi Kerja dan Kesejahteraan Guru terhadap Kinerja Guru MI di Kecamatan Jekulo - Ma'rifah, Ishfina Ziyadatul (QUALITY, 2023)
The Effect of Work Motivation and Teacher Welfare on the Performance of MI Teachers in Jekulo District. This study analyses the influence of work motivation and teacher welfare on the performance of MI teachers in Jekulo sub-district. To improve teacher performance, it is recommended that attention is given to both work motivation and teacher welfare. Specifically, it aims to investigate the impact of work motivation and teacher welfare on teacher performance. The findings suggest that the decline in teacher performance is influenced by work motivation and teacher welfare. The study employed a quantitative approach and survey research type with 91 private teachers as subjects. Data was collected using questionnaires and documentation, and analyzed using multiple linear regression analysis. The questionnaire was validated by two expert lecturers and Aiken's validity was calculated.  The results indicate that work motivation and teacher welfare have a significant influence on teacher performance. Based on the F count value being greater than the F table value (69.144 > 3.10), Ho is rejected and Ha is accepted. This indicates a significant influence between Work Motivation and Teacher Welfare on Teacher Performance in MI Jekulo sub-district. Penelitian bertujuan untuk menganalisis pengaruh: 1) Motivasi kerja terhadap kinerja guru; 2) Kesejahteraan guru terhadap kinerja guru; 3) Motivasi kerja dan kesejahteraan guru terhadap kinerja guru. Menurunnya kinerja guru dipengaruhi motivasi kerja dan kesejahteraan guru. Penelitian menggunakan pendekatan kuantitatif dan jenis penelitian survey yang subjeknya 91 guru swasta. Pengumpulan data dengan kuesioner dan dokumentasi, menggunakan analisis regresi linear berganda. Instrumen kuesioner divalidasi dua dosen ahli kemudian dianalisis, dihitung dengan validitas Aiken. Hasil penelitian menunjukkan: 1) Terdapat pengaruh motivasi kerja terhadap kinerja guru. 2) Terdapat pengaruh kesejahteraan guru terhadap kinerja guru. 3) Terdapat pengaruh signifikan antara motivasi kerja dan kesejahteraan guru terhadap kinerja guru. Dilihat pada nilai F hitung > F tabel (69,144 > 3,10). Artinya Ho ditolak dan Ha diterima, artinya terdapat pengaruh yang signifikan antara Motivasi Kerja dan Kesejahteraan Guru terhadap Kinerja Guru MI kecamatan Jekulo.